MOTIVASI PENCALONAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH MENJADI ANGGOTA DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA ASAL RIAU PADA PEMILIHAN UMUM 2014 - Erwinda "; Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research present describe the motivation of nomination legislators to be Regional Representative Council member from Riau Province in 2014 election. In this election, was founding many of the legislators who have the background of political parties prefer to be a Representatative Council member, which are known is independent. Of the 25 candidates DPD registered in KPU, seen 6 names are legislators. They are Desmianto and H. Said Zohrin, S.H., MH which are member of Pekanbaru legislators, then there’s that comes from DPRD Riau Province, namely is Iwa Sirwani Bibra, S.Sos., M.Si, H. Zulkarnain, S.H., MH, dan H.Ilyas Labay, S.Sos., M.Si. Further Afri, S.P who are the member of Kuantan Singingi Regency legislator.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. Researcher collect data from books, government regulation, journal, mass media, website, and deep interview with informan who are knowing about the phenomenon in this research.The conclution of this research are motivation of the candidates DPD RI who was from legislators are wanted to defend the aspiration of Riau community. They want to get into state agencies DPD RI because wanted to defend the regional aspiration are still many failure, without intervention from another including from political parties.Keywords : Motivation, Election, State Agencies